Improving 3–5 Year Old Children’s Vocabulary, Listening, and Speaking Skills of English as a Second Language through Sociodramatic Play - Dian Septia (Jurnal Teropong Pendidikan, 2022)
The purposes of this study were to analyze 3–5 year old children’s vocabulary, listening and speaking skills as they engaged in sociodramatic play that was set around air transportation theme. The classroom action research design for this study was done in three cycles. It utilized an opportunity that the teacher provided for fourteen research subjects to use language for multiple functions within the context of sociodramatic play by encouraging the subjects to listen to other people, and to speak up their feelings and ideas by implementing the vocabulary they have learned. The data analysis in this research showed that the implementation of sociodramatic play improved the vocabulary, the listening and the speaking skills of 3–5 year old nursery children of ABC school.